On the weak differentiability of u° f^-1
Let p≥ n-1 and suppose that f:Ω→R^n is a homeomorphism in the Sobolev space W^1,p_(loc (Ω,R^n). Further let uW^1,q_(loc (Ω) where q=pp-(n-1) and for q>n we also assume that u is continuous. Then u° f^-1(BV_(loc (f(Ω)) and if we moreover assume that f is a mapping of finite distortion, then u° f^-1W^1,1_(loc (f(Ω))., number=2, journal=MATHEMATICA SCANDINAVICA, author=Hencl, Stanislav, year=2010, month=Dec., pages=198–208